Targeting of externalized αB-crystallin on irradiated endothelial cells with pro-thrombotic vascular targeting agents: Potential applications for brain arteriovenous malformations. Issue 189 (May 2020) - Subramanian, Sinduja; Zhao, Zhenjun; Faqihi, Fahimeh; Grau, Georges E.; Combes, Valery; Inglis, David W.; Moutrie, Vaughan; Stoodley, Marcus A.; McRobb, Lucinda S.
Abstract: Background: Vascular targeting uses molecular markers on the surface of diseased vasculature for ligand-directed drug delivery to induce vessel occlusion or destruction. In the absence of discriminatory markers, such as in brain arteriovenous malformations (AVMs), stereotactic radiosurgery may be used to prime molecular changes on the endothelial surface. This study explored αB-crystallin (CRYAB) as a radiation induced target and pre-tested the specificity and efficacy of a CRYAB-targeting coaguligand for in vitro thrombus induction. Methods: A parallel-plate flow system was established to circulate human whole blood over a layer of human brain endothelial cells. A conjugate of anti-CRYAB antibody and thrombin was injected into the circuit to compare binding and thrombus formation on cells with or without prior radiation treatment (0–25 Gy). Results: Radiation increased CRYAB expression and surface exposure in human brain endothelial cells. In the parallel-plate flow system, the targeted anti-CRYAB–thrombin conjugate increased thrombus formation on the surface of irradiated cells relative to non-irradiated cells and to a non-targeting IgG-thrombin conjugate. Fibrin deposition and accumulation of fibrinogen degradation products increased significantly at radiation doses at or above 15 Gy with conjugate concentrations of 1.25 and 2.5 μg/mL. Conclusions: CRYAB exposure can be detected at the surface of human brain endothelial cells in response to irradiation. Pro-thrombotic CRYAB-targeting conjugates can bind under high flow conditions and in the presence of whole blood induce stable thrombus formation with high specificity and efficacy on irradiated surfaces. CRYAB provides a novel radiation marker for potential vascular targeting in irradiated brain AVMs. Highlights: Radiation stimulates CRYAB translocation to the surface of human endothelial cells. Surface CRYAB is accessible to vascular targeting agents delivered under high flow. CRYAB-targeting coaguligands induce selective thrombosis on irradiated cells. Parallel-plate flow chambers are useful for pre-testing vascular targeting agents.